Solar - photocatalytic of zinc oxide for mineralization of phenol - Nik Noor Athirah Nik Yusoff (School of Environmental Engineering, Universiti Malaysia Perlis, 2014)
The photocatalytic degradation of phenol was investigated with zinc oxide (ZnO) as photocatalyst under solar light irradiation. Operating parameters such as initial phenol concentration, catalyst loading, pH, effect of aeration, H2O2 dosage and effect of solar light irradiation were investigated. The low initial concentration of phenol indicates more efficient photocatalytic degradation. The optimum catalyst loading to provide sufficient active site for the photocatalytic activity is 0.6 g